Spectral analysis of Urvara–Yalode bright areas on Ceres suggests a new aromatic organic material and Fe-carbonate - S. D’Urzo; A. Raponi; M.C. De Sanctis; B. Ranieri; M. Ciarniello; F.G. Carrozzo; M. Ferrari; E. Ammanito; A. Frigeri; S. De Angelis; M. Formisano (Icarus, 2027)

Making Waves: towards a harmonized approach for monitoring antimicrobial resistance in European surface waters - P. Krzeminski; C.U. Schwermer; M. Anglès d’Auriac; H. Bürgmann; H. Schmitt; J. Vierheilig; M. Gjeitnes; S.J. Moe; X. Bellanger; R. Carapeto García; P. Crespo Iniesta; C. Dagot; et al. (Water Research, 2026)

Successful outcome of open distal interphalangeal joint luxation in equids treated by surgical debridement without internal implants - L. C. Ferrari; E. V. P. Apolonio; S. L. de Oliveira-Gonçalves; A. L. A. Rambo; J. V. Bergamasco; J. M. Alonso; M. J. Watanabe; A. L. G. Alves (Veterinary Research Communications, 2026)
Introduction The distal interphalangeal joint (DIPJ) plays a crucial role in the function of the hoof and digit. Dislocations and subluxations in this region are rare and primarily of traumatic origin. Case Report This case report aims to describe two unusual cases of open DIPJ dislocation, including clinical presentation, diagnostic workup, treatment, and long-term follow-up. Both animals presented with open traumatic distal interphalangeal joint (DIPJ) luxation. In Case 1, the animal received initial care on the property 5 h post-trauma and presented with joint exposure and articular surface contact with the ground. In Case 2, the animal was referred to the veterinary hospital without prior care, 3 h post-trauma, but there was no contact of the articular surface with the ground. Both animals showed grade 5/5 lameness (AAEP). The animals underwent general anesthesia, joint lavage, regional intravenous perfusion with antibiotics, debridement of devitalized tissues, skin synthesis, and immobilization with synthetic casting. During immediate recovery and hospitalization, a grade 4/5 lameness persisted. Long-term radiographic control revealed the development of degenerative joint disease in both animals. After 3 and 2 years, respectively, animals 1 and 2 showed persistent lameness (grade 2/5) with an absence of local sensitivity. Conclusion The conservative treatment employed in these cases of open DIPJ luxation proved effective for the maintenance of the patients’ lives, and although the infectious pathological process invariably progressed to osteoarthritis, the evolution of the clinical conditions allowed for light exercise and maintenance of reproductive activity.

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Circulating metabolites and fatty acids associated with ultra-processed food consumption: results from the EPIC study - Jessica Blanco-Lopez; Sahar Yammine; Joseph A. Rothwell; Mathilde His; Carine Biessy; Pekka Keski-Rahkonen; Bernadette Chimera; Inarie Jacobs; Aline Al Nahas; Emine Koc Cakmak; Oliver Robinson; Fernanda Morales Berstein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Challenges in estimating wolf population size using spatial count models and camera trap data - M.V. Boiani; P. Dupont; R. Bischof; O. Friard; F. Bisi; G. Bombieri; S. Calderola; S. Carolfi; C. Chioso; U. Fattori; P. Ferrari; S. Filacorda; et al. (Biological Conservation, 2026)

3D Contractile and Remodeling Behaviors of Functionally Normal and Prolapsed Human Mitral Valve Interstitial Cells - Toni M. West; Gabriel Peery; Sanjana S. Chemuturi; Jodie H. Pham; Giovanni Ferrari; Micheal S. Sacks (Annals of Biomedical Engineering, 2026)
Purpose Mitral valve prolapse (MVP) can lead to heart failure, arrhythmia, and death. Current treatments for MVP are strictly surgical, while alternative therapies remain elusive due to lack of knowledge of underlying processes. Importantly, our understanding of cellular mechanisms of post-MVP repair remodeling that can lead to secondary surgery remain limited. We therefore explored how MVP affects human mitral valve interstitial cell (MVIC) extracellular matrix (ECM) remodeling and basal contractility. Methods Isolated MVP and physiologically normal MVICs were embedded in poly(ethylene) glycol-based hydrogels containing fluorescent microbeads (~ 1 μm) and imaged in the basal and deactivated states. 3D cell surface tractions and changes in MVIC hydrogel local moduli were then determined via inverse computational mechanics modeling. Results Hydrogel softening occurred further from MVIC surfaces, whereas pronounced stiffening occurred in close proximity, a result of collagen deposition as verified by collagen staining. MVP MVICs induced greater hydrogel stiffening and less degradation than normal MVICs. Interestingly, even though MVP MVICs had higher basal contractile displacements, their traction forces and hydrogel strain energy densities were significantly lower than those of normal MVICs. Conclusion These findings elucidate, for the first time, that MVP MVICs have significantly altered contractile and ECM remodeling behaviors compared to functionally normal MVICs. This result suggests that MVIC behaviors may affect how MVP responds to repair. Moreover, as our studies were performed on isolated MVICs, our observed differences in MVIC behaviors are intrinsic to MVIC phenotype and are not only due to the altered cellular microenvironment.

Incorporation of dose-rate effects into the BIANCA biophysical model and application for space radiation risk assessment - E.I. Canay; M. Carante; A. Casali; E. Bernardini; D. Dondi; Dhanalakshmi Vadivel; L. Cansolino; E. Delgrosso; C. Ferrari; M. Pullia; F. Bonforte; J. Riback; et al. (Life Sciences in Space Research, 2026)

ISRM Suggested Methods for Triaxial Compression Testing of Shales and Mudstones - R. Ewy; E. Fjær; P. Delage; D. Dewhurst; J. Dudley; A. Ferrari; S. Giger; M. Soldal; J. Stenebråten; B. Crawford; S. Fontoura; L. Grande (Rock Mechanics and Rock Engineering, 2026)

Covalently bound Eosin Y on chitosan as a removable photosensitizer for ranitidine degradation - Julieta L. Sacchetto; Alberto M. Barrera Llorente; Marcela Kuhn Beldomenico; José Natera; María J. Gramaglia; Gabriela Porcal; Silvana Plem; Gabriela V. Ferrari; Walter A. Massad (Chemosphere, 2026)

Rivers under stress: geochemical changes along a rural–urban gradient during extreme hydrological events (Greve River, Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2026)
Rivers are increasingly exposed to combined anthropogenic and climate-driven pressures, particularly along rural-to-urban gradients where land use, population density, and contaminant sources progressively intensify downstream. In parallel, prolonged droughts followed by intense rainfall events are becoming more frequent, potentially enhancing contaminant accumulation during dry periods and their rapid mobilization during subsequent first-flush events. However, the interactions between these hydrological extremes and spatial anthropogenic gradients in controlling river geochemistry remain insufficiently understood. This study investigates the spatial and seasonal evolution of river chemistry along the Greve River (Tuscany, Italy), a tributary of the Arno River, characterized by a marked rural-to-urban transition, during the exceptional 2022 European drought and subsequent heavy rainfall event. Six sampling campaigns were conducted between May and October 2022, combining high-resolution spatial monitoring with geochemical and isotopic tracers, including total dissolved solids (TDS), nutrients, and trace elements. The results reveal a progressive downstream enrichment in anthropogenic tracers (e.g., NO 3 − and K + , up to 9 mg/L and 6.6 mg/L, respectively) and pronounced evaporative isotope enrichment during the driest months (slope of the evaporation line ~ 4), indicating strong hydrological stress conditions. The first intense rainfall event triggered rapid remobilization of accumulated material and heterogeneous contaminant transport dynamics. Elevated nutrient concentrations (e.g., NH 4 + , up to 1.4 mg/L) in downstream sectors further reflect the combined influence of hydrological stress and urban inputs. These findings demonstrate how climate-driven hydrological extremes can amplify contaminant mobilization along urbanized river continuums. The integration of isotopic and geochemical tracers provides a transferable framework for assessing water-quality vulnerability in river basins increasingly exposed to hydroclimatic instability.

Global overview of progress in respecting the contributions of traditional knowledge in biodiversity governance - Kinga Öllerer; Pernilla Malmer; Marianna Biró; Noor Noor; Polina Shulbaeva; Maurizio Farhan Ferrari; Suneetha M. Subramanian; András Báldi; Zsolt Molnár (Conservation Biology, 2026)
Recognition and engagement of Indigenous Peoples and local communities (IP&LCs) and other traditional knowledge (TK) holders in formal biodiversity governance remain limited, despite their significant contribution to the conservation and sustainable use of biodiversity through their knowledge, innovations, practices, and land stewardship. We conducted the first global assessment of how the 195 countries that ratified the Convention on Biological Diversity self‐report on this contribution based on a full content analysis of all of the 2 most recent national reports (NR5 and NR6). The number of countries self‐reporting IP&LC and TK roles in the conservation and sustainable use of biodiversity increased between the 2 reporting periods and exceeded 55% for NR6. The mention of IP&LC and TK contribution to cultivation and domestication was slightly higher; 59% of countries provided evidence of recognition of this contribution in their NR6. Reference to the holders themselves was much lower, even in the case of cultivation and domestication, and explicit evidence of IP&LC involvement in reporting was minimal, particularly in developed countries. Several reports, particularly European submissions, mentioned traditional land use or community‐based practices but considered addressing IP&LCs and TK irrelevant due to terminology confusion. Ahead of the next reporting (NR7), due in 2026, and in line with the Kunming–Montreal Global Biodiversity Framework, which recognizes IP&LCs and TK as integral to its goals, we urge governments to strengthen engagement with IP&LCs and other TK holders, develop and respect partnerships that incorporate their knowledge, practices, and rights, support IP&LC‐led conservation, and build on these partnerships in monitoring and reporting on national progress. We aimed to support this process with short‐term practical recommendations for upcoming reporting and longer‐term strategic guidance and a dataset of illustrative quotes from the analyzed national reports as examples of good practice.

Association of meeting the 24-hour movement guidelines with heart rate variability in adults - Bruna T. C. Saraiva; William R. Tebar; Debora T. Furuta; Stefany C. B. Silva; Ewerton P. Antunes; Guilherme Sousa; Gerson Ferrari; Luiz Carlos M. Vanderlei; Diego Giulliano Destro Christofaro (European Journal of Applied Physiology, 2026)

Scaling what works: a collaborative capacity-building program tailored to optimize resources and scale evidence-based interventions for cancer prevention and control - Mary Wangen; Jingle Xu; Amy Tran; Elizabeth A. Rohan; Prajakta Adsul; Cam Escoffery; Renée M. Ferrari; Nikki Hayes; Cari Herington; Katie Jones; Jaron Hoani King; Julie Kranick; et al. (Cancer Causes & Control, 2026)

Dietary Paecilomyces variotii single-cell protein supports growth and intestinal health in gilthead sea bream - Serena Busti; Trond M Kortner; Elin Christine Valen; Elisa Benini; Alessio Bonaldo; Charilaos Xiros; Fabio Brambilla; Daniel Scicchitano; Giorgia Palladino; Marco Candela; Marco Berrettini; Francesco Dondi; et al. (Aquaculture, 2026)

Yield and protein gaps in barley: Quantifying nitrogen and sulfur contributions - Federico M. Gomez; Flavio H. Gutiérrez-Boem; Pablo Prystupa; Jorge L. Mercau; Jose J. Boero; Gustavo Ferraris; Leonor G. Abeledo (European Journal of Agronomy, 2026)

Multidisciplinary monitoring of mud volcanoes: a new perspective on fluids and seismicity link from the Salse di Nirano (Italy) - E. Ferrari; A. L. Rizzo; G. Capelli Ghioldi; A. Sciarra; G. Tamburello; F. Viveiros; S. Lovati; M. Massa (Natural Hazards, 2026)
Understanding the relationship between fluids and seismicity is crucial for improving seismic hazard assessment, as fluid migration can play a significant role in earthquake triggering. Here, we present the results from an innovative real-time multiparametric monitoring implemented at the so-called ‘Salse di Nirano’ or mud volcano field (Northern Apennines, Italy), a region of medium to high seismic hazard. The objective is to investigate how geofluid dynamics relate to local seismicity. Two bubbling mud pools were selected for continuous monitoring of mud level, temperature, and electrical conductivity. Additionally, a CO 2 flux station was installed on the field’s edge, where elevated gas emissions are observed. Complementary meteorological and seismic stations track atmospheric conditions and seismic activity. Notably, anomalous shifts in mud pool electrical conductivity and soil CO 2 flux were recorded in temporal correlation with two distinct seismic swarms in 2024, highlighting the potential of fluid-geochemistry monitoring as a tool for tracking subsurface processes linked to seismic unrest.

Surveying Shared Marine Resources at a Regional Scale: Connectivity and Differentiation of Round Sardinella in Eastern Mediterranean - Alice Ferrari; Giusy Catalano; Valentina Crobe; Alessia Cariani; Emre Keskin; Pierluigi Carbonara; Loredana Casciaro; Reda M. Fahim; Sharif Jemaa; Savaş Kılıç; Myriam Lteif; Abdalnasser S. H. Madi; et al. (Fishes, 2026)
The round sardinella (Sardinella aurita Valenciennes, 1847) is a widely distributed migratory pelagic fish inhabiting the Mediterranean Sea and the eastern Atlantic coasts. The species is heavily exploited and represents a valuable resource for global fisheries. In the Mediterranean area, uptakes of round sardinella are particularly high in the Ionian and Levant regions, where landings have shown fluctuating yet significant peaks in recent decades. Given its migratory nature, understanding the connectivity among populations is crucial for delineating appropriate fishery management units. Previous studies employing morphometric, meristic, and molecular analyses have yielded mixed results regarding population structuring. Here, the genetic differentiation among Eastern Mediterranean S. aurita populations was investigated using a multi-marker approach: the mitochondrial cytochrome c oxidase subunit I (COI), cytochrome b (CytB), control region (CR), and 16S ribosomal RNA (16S rRNA), and seven species-specific nuclear simple sequence repeats (SSRs). Overall, the results indicate high genetic diversity coupled with weak population structuring across the Eastern Mediterranean. These analyses aim at clarifying stock boundaries towards supporting sustainable management strategies at a regional scale for this ecologically and economically important species.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Development of biochar-immobilized Bacillus subtilis BEIB-18 for hexavalent chromium (Cr(VI)) bioremediation in aqueous medium - V. A. Schommer; M. T. Nazari; A. P. Vanin; D. D. C. Krein; N. Melo; L. F. dos Santos; G. L. Dotto; V. Ferrari; L. M. Colla; A. Dettmer; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Sustainable digitalisation - a system thinking approach for determining costs and benefits in the agri-sector - K. Soma; G. Brunori; C. Giagnocavo; F. Meulman; M. Ryan; R.M. Heredia Hortigüela; C. Iliopoulos; M. Paulus; A. Ferrari; E. Kilis; S. Grando; V. Bellon-Maurel; et al. (Agricultural Systems, 2026)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Prevalence and consequences of microplastic ingestion in the world's southernmost insect, Belgica antarctica - Jack J. Devlin; Cleverson Lima; Yuta Kawarasaki; J.D. Gantz; Vitor A.C. Pavinato; Marco Scaramelli; Valentina Ferrari; Lisa Vaccari; Giovanni Birarda; Elisa Bergami; Andrew P. Michel; Peter Convey; et al. (Science of The Total Environment, 2025)

Dinner or dismay? Altered behavioural response of crayfish to alarm cues when fed a conspecific diet - Gabrielle H. Achtymichuk; Kaitlyn M. Fish; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2025)

The Genetics of Host Plant Acceptance in Pea Aphids - Isobel Eyres; Hannah Fenton; Jean Christophe Simon; Jean Peccoud; Julia Ferrari; Roger Butlin; Carole M. Smadja (Molecular Ecology, 2025)
The evolution of host‐associated sympatric populations in phytophagous insects (so called “host races”) connects adaptive divergence to barriers to gene flow. Pea aphid ( Acyrthosiphon pisum ) host races specialise on legume species, and because host plant choice leads to assortative mating, the genetic basis of host plant acceptance is key to understanding speciation. Aphids use smell and taste in their host plant selection. While chemosensory genes frequently emerge as “outliers” in genome scans, their link to plant acceptance behaviour remains unclear. We examined the genetic basis of host‐associated phenotypes using an F2 cross between two pea aphid host‐associated races (specialised on alfalfa— Medicago sativa ‐ and pea— Pisum sativum ), assaying behaviour on both host plants and conducting QTL and regional heritability analyses based on a high‐resolution linkage map. We identified five regions of moderate effect associated with acceptance of alfalfa, two with pea acceptance and two with survival on alfalfa. Two QTLs, one for alfalfa and one for pea acceptance, are located within a large rearranged region on chromosome 1, while other QTLs linked to alfalfa acceptance and survival are in the same region on chromosome 3—linking host plant choice to fitness. These findings highlight the polygenic basis of acceptance behaviour and the role of gene clustering and chromosomal rearrangements in promoting coupling among barrier loci. We identified 60 chemosensory genes within regions connected to acceptance, 24 of which were divergent among pea aphid races in previous genome scan or gene expression analyses. Evidence linking these genes to acceptance phenotypes supports their role in determining host plant specificity and as barrier loci contributing to pea aphid speciation.

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Fibroblast Activation Protein (FAP) as a possible therapeutic target in selected canine malignant tumours - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; V. Balbi; G. Bianchi; et al. (Journal of Comparative Pathology, 2025)

Analysis of tight junction protein dynamics by immunohistochemistry in porcine intestinal epithelial cells (IPEC-J2) cells exposed to osmotic stress - B. Passeri; P. Borghetti; M. Andrani; M. Di Pentima; A. Luppi; E. De Angelis; V. Cavalli; L. Ferrari; R. Saleri (Journal of Comparative Pathology, 2025)

Splice me up, scotty: Extra domain-B fibronectin in canine tumours puts a spotlight on melanoma - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; A. Verdi; D. Neri; et al. (Journal of Comparative Pathology, 2025)

Integrating time of exposure into quantitative evolving rockfall hazard assessment for open-pit mining - F. Bahootoroody; A. Giacomini; K. Thoeni; D.E. Guccione; F. Ferrari; M. Jaboyedoff (International Journal of Rock Mechanics and Mining Sciences, 2025)

Fate-tracking early coral recruits following bleaching in a remote reef ecosystem - John E. Stratford; Andrew O. M. Mogg; Heather J. Koldewey; Liam Lachs; Renata Ferrari; James Guest; Daniel T. I. Bayley (Coral Reefs, 2025)
As coral reefs face increasingly frequent and severe disturbances, their condition relies more heavily on recovery dynamics. Understanding reef recovery is essential for assessing the long-term ecological integrity and functioning of these ecosystems. In this study, we used structure-from-motion photogrammetry to map reefs at Peros Banhos atoll (Chagos Archipelago) in the three years following the 2015–2016 mass coral bleaching event. This approach enabled us to detect and track individual post-bleaching coral recruits underpinning natural recovery ( n = 1,074 across 72 m 2 ), and investigate their early survival and growth. In 2017, one year after the bleaching, new recruit density was highest, largely due to comparatively high recruitment in sheltered sites. However, 2018 recruits had higher first-year survival and growth than the 2017 cohort, suggesting a negative legacy effect of high temperatures on reef recovery. Branching coral taxa showed both the highest first-year survival and growth. Interestingly, fine-scale substrate complexity at the onset of recovery was negatively associated with the density of recruits 1–2 years later. Despite favourable conditions that allowed the majority of recruits to survive and grow rapidly, all recruits combined accounted for only 2.39% coral cover three years after the bleaching event. Our results document vital rates during early natural recovery at a remote protected atoll and shed light on the dynamics of coral recruits immediately following mass bleaching. Further, we demonstrate the insight that photogrammetric approaches can provide to reef demographic studies.

P18-57 Assessing cardiotoxicity of compounds in a 3D Heart-on-Chip platform by evaluating alterations in cardiac electrophysiology and contractility - C. Pernici; M. Mondini; M. Rasponi; E. Ferrari; R. Visone; P. Occhetta (Toxicology Letters, 2025)

Time Distributed Deep Learning Models for Purely Exogenous Forecasting: Application to Water Table Depth Predictions Using Weather Image Time Series - Matteo Salis; Abdourrahmane M. Atto; Stefano Ferraris; Rosa Meo (Environmental Modelling & Software, 2025)

Left atrial size in healthy Cavalier King Charles spaniels: a comparison to dogs of other breeds and previously published reference intervals - D. Caivano; P. Ferrari; M. Rishniw (Journal of Veterinary Cardiology, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Microplastic consumption elevates fish oxidative stress but does not affect predator-driven mortality - Amelia M. Mannering; David J. Burritt; Valeriya Komyakova; Maud C.O. Ferrari; George Vamvounis; Alexandra M. Gulizia; Adam Staples; Mark I. McCormick; Bridie J.M. Allan (Science of The Total Environment, 2025)

Skull roof anatomy of the Early Jurassic (Toarcian) acipenseriform †Gyrosteus mirabilis Woodward ex Agassiz, from Yorkshire, England, elucidates diversity of †Chondrosteidae - Samuel L.A. Cooper; Megan Jacobs; Lucrezia Ferrari; David M. Martill (Proceedings of the Geologists' Association, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Traditional and low-cost technical approaches for investigating greenhouse gases and particulate matter distribution along an urban-to-rural transect (Greve River Basin, Central Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2025)
Human activities, largely tied to fossil fuels and intensive agriculture, emit massive amounts of climate-altering species and harmful pollutants into the atmosphere that affect soil, ecosystems, and water. Air quality monitoring is crucial to minimize harmful effects and protect human and environmental health. The Greve River basin (Tuscany, central Italy) represents an excellent example of an ecosystem affected by various anthropogenic air contaminants. The upstream areas are predominantly rural, while the downstream zones are characterized by urban and industrial development. Air pollutants throughout the basin were measured adopting two strategies: (i) fixed monitoring at five sites using multiparametric stations equipped with low-cost sensors for CO 2 , CH 4 , and PM 2.5 concentrations; (ii) measurements along a transect using a mobile monitoring station equipped with a Picarro G2201- i analyzer for the determination of CO 2 and CH 4 concentrations and 13 C/ 12 C values of the two gases. Results revealed relatively high CO 2 and CH 4 concentrations downstream, mainly due to vehicular traffic based on the isotopic signature. The temporal and spatial distribution of the contaminants mirrored the evolution of the Planetary Boundary Layer, with peak concentrations in the early morning due to stable atmospheric conditions, and contaminant dilution due to air turbulence during the daytime. Particulate (PM 2.5 ) distribution showed a trend similar to gaseous pollutants, being strongly dependent on wind speed and rainfall events. The high spatiotemporal resolution of data acquisition provided by the low-cost stations for air quality measurements represents an important advance for developing monitoring strategies, complementing the traditional instrumentation commonly used by agencies.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Wastewater based measures of COVID-19 and associations with children's absenteeism at grade schools - Helena M. Solo-Gabriele; Gabriela Guevara; Naresh Kumar; Ayaaz Amirali; Kristina M. Babler; Cynthia C. Beaver; Samuel Comerford; Maria Ferraris; Natasha Schaefer Solle; Mark E. Sharkey; Lisa Gwynn (Science of The Total Environment, 2025)

Fine-scale landscape heterogeneity drives microbial community structure at Robinson Ridge, East Antarctica - Sin Yin Wong; Nathali M. Machado-de-Lima; Daniel Wilkins; Eden Zhang; Belinda C. Ferrari (Science of The Total Environment, 2025)

Evaluation of methods for detection of Campylobacter in raw milk: A multi-country study - Ásgeir Ástvaldsson; Gunnar Andersson; Linda Svensson; Karin Bruckner; Martine Denis; Sevinc Ferrari; Olwen Golden; Janine Heise; Moa Lavander; Elisabeth Repérant; Hilde M. Riedel; Kerstin Stingl; et al. (International Journal of Food Microbiology, 2025)

A Rapid Method to Identify the Effects of Coastal Artificialization on Posidonia oceanica Meadows in Coves - M. Ferrari; L. Carpi; M. Montefalcone (Estuaries and Coasts, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Spatial Variation in Upper Limits of Coral Cover on the Great Barrier Reef - Mariana Álvarez‐Noriega; Juan C. Ortiz; Daniela M. Ceccarelli; Michael J. Emslie; Katharina E. Fabricius; Michelle J. Jonker; Marji Puotinen; Barbara J. Robson; Chris M. Roelfsema; Tane H. Sinclair‐Taylor; Renata Ferrari (Global Ecology and Biogeography, 2024)
Aim Identifying the maximum coral cover that a coral community can sustain (i.e., its ‘upper limit’) is important for predicting community dynamics and improving management strategies. Here, we quantify the relationship between estimated upper limits and key environmental factors on coral reefs: hard substrate availability, temperature and water clarity. Location Great Barrier Reef (GBR), Australia (over 1400 km). Time Period 1990 to 2022. Major Taxa Studied Scleractinian corals. Methods We used 32 years of data on coral cover around reef perimeters. Each reef was divided into four wave‐exposure habitats depending on prevailing wind conditions. For each site, we determined if hard coral cover had reached a plateau or upper limit. Next, we extracted existing estimates of hard substrate availability, modelled water temperature and Secchi depth. Then, we quantified the relationship between these environmental variables and the upper limits. Results We found varying upper limits across the GBR, with a median of 33% coral cover and only 17% of the estimated upper limits exceeded 50% coral cover. Upper limits increased towards the southern reefs. Our results show that upper limits increased with increasing hard substrate availability and decreased with temperature and, to a lesser extent, with water clarity. Main Conclusions The upper limits estimated in this study are much lower than what is commonly assumed when modelling ecological dynamics, most likely resulting in predicted recovery rates being inappropriately high. Although hard substrate ultimately restricted upper limits, there are mechanisms constraining the proportion of hard substrate that is covered by hard corals. The negative relationship between temperature and upper limits cannot be explained by changes in macroalgal abundance but may be related to changes in species composition. The quantitative relationships between the upper limits of coral cover and environmental variables will provide critical information to prioritise sites for management interventions.

Deoxynivalenol induces ovarian damage and uterine changes in prepubertal and adult mice - G.A.A. Lemos; J.R. Gerez; J.B. Costa; E.J. Venâncio; M. Souza; P.O. Favaron; J.R. Greghi; E.M. Gloria; L. Staurengo-Ferrari; W.A. Verri; A.P.F.R.L. Bracarense (Toxicon, 2024)

Cytogenetic analysis of meiotic behaviour and stability in a trigeneric hybrid (triticale x trigopiro) - M. Fradkin; E. J. Greizerstein; E. Grassi; V. Ferreira; M. R. Ferrari; L. Poggio (Protoplasma, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The use of fishery and aquaculture by-products with Nannochloropsis sp. allows total dietary replacement of wild-caught fishmeal, fish oil and soy protein in European sea bass juveniles - A. Marchi; E. Benini; F. Dondi; M.G. Ferrari; D. Scicchitano; G. Palladino; M. Candela; R. Cerri; A. Di Biase; A.J. Vizcaíno; F.J. Alarcón-López; F.G. Acién; et al. (Aquaculture, 2024)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Insights from an extensive triaxial testing campaign on a shale for comparative site characterization of a deep geological repository - E. Crisci; S.B. Giger; L. Laloui; A. Ferrari; R. Ewy; R. Stankovic; J. Stenebråten; K. Halvorsen; M. Soldal (Geomechanics for Energy and the Environment, 2024)

Remaining Loyal to Our Soil: A Prospective Integrated Assessment of Soil Erosion on Global Food Security - Martina Sartori; Emanuele Ferrari; Robert M'Barek; George Philippidis; Kirsten Boysen-Urban; Pasquale Borrelli; Luca Montanarella; Panos Panagos (Ecological Economics, 2024)

Photosensitized oxygenation reactions as an alternative towards the degradation of fenamates and related pollutants using visible light - Eduardo L. Gutiérrez; Julieta Sacchetto; Francisco Boscá; M. Luisa Marín; Walter Massad; M. Paulina Montaña; Sandra Miskoski; Gabriela V. Ferrari (Journal of Water Process Engineering, 2024)

Enteric associated T-cell lymphoma in a mule - Giovanna G. de Souza; Zara A. Lacerda; Fernanda B.C. de Moura; Isabeli J. Contel; Shéron L. de Oliveira; Lorena C. Ferrari; Emanuel V.P. Apolonio; Juliana de M. Alonso; Ana Liz G. Alves; Noeme S. Rocha (Journal of Equine Veterinary Science, 2024)

A Global Systematic Literature Review of Ecosystem Services in Reef Environments - Vinicius J. Giglio; Anaide W. Aued; Cesar A. M. M. Cordeiro; Linda Eggertsen; Débora S. Ferrari; Leandra R. Gonçalves; Natalia Hanazaki; Osmar J. Luiz; André L. Luza; Thiago C. Mendes; Hudson T. Pinheiro; Bárbara Segal; et al. (Environmental Management, 2024)

Combination of pH-shifting, ultrasound, and heat treatments to enhance solubility and emulsifying stability of rice protein isolate - Daniela E. Igartúa; M. Celeste Dichano; Sofia B. Ferrari; Gonzalo G. Palazolo; Dario M. Cabezas (Food Chemistry, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

Influence of Weather Conditions on Sleeping Patterns and Selection of Foliage Cover of Sleeping Trees in Black-and-Gold, Howler Monkeys (Alouatta caraya) in Northern Argentina - Melina V. Brividoro; Luciana I. Oklander; Verónica I. Cantarelli; Marina F. Ponzio; Héctor R. Ferrari; Martín M. Kowalewski (International Journal of Primatology, 2023)

Patient preferences for the design of a pharmacy-based colorectal cancer screening program - Alison T. Brenner; Austin R. Waters; Mary Wangen; Catherine Rohweder; Olufeyisayo Odebunmi; Macary Weck Marciniak; Renée M. Ferrari; Stephanie B. Wheeler; Parth D. Shah (Cancer Causes & Control, 2023)
Purpose To assess preferences for design of a pharmacy-based colorectal cancer (CRC) screening program (PharmFIT™) among screening-eligible adults in the United States (US) and explore the impact of rurality on pharmacy use patterns (e.g., pharmacy type, prescription pick-up preference, service quality rating). Methods We conducted a national online survey of non-institutionalized US adults through panels managed by Qualtrics, a survey research company. A total of 1,045 adults (response rate 62%) completed the survey between March and April 2021. Sampling quotas matched respondents to the 2010 US Census and oversampled rural residents. We assessed pharmacy use patterns by rurality and design preferences for learning about PharmFIT™; receiving a FIT kit from a pharmacy; and completing and returning the FIT kit. Results Pharmacy use patterns varied, with some notable differences across rurality. Rural respondents used local, independently owned pharmacies more than non-rural respondents (20.4%, 6.3%, p < 0.001) and rated pharmacy service quality higher than non-rural respondents. Non-rural respondents preferred digital communication to learn about PharmFIT™ (36% vs 47%; p < 0.001) as well as digital FIT counseling (41% vs 49%; p = 0.02) more frequently than rural participants. Preferences for receiving and returning FITs were associated with pharmacy use patterns: respondents who pick up prescriptions in-person preferred to get their FIT (OR 7.7; 5.3–11.2) and return it in-person at the pharmacy (OR 1.7; 1.1–2.4). Conclusion Pharmacies are highly accessible and could be useful for expanding access to CRC screening services. Local context and pharmacy use patterns should be considered in the design and implementation of PharmFIT™.

WRF data assimilation of weather stations and lightning data for a convective event in northern Italy - E. C. Maggioni; T. Manzoni; A. Perotto; F. Spada; A. Borroni; M. Giurato; M. Giudici; F. Ferrari; D. Zardi; R. Salerno (Bulletin of Atmospheric Science and Technology, 2023)

Ethanol Production from Eucalyptus Sawdust Following Sequential Alkaline Thermochemical Pretreatment with Recovery of Extractives - M. Guigou; S. Moure; F. Bermúdez; L. Clavijo; M. N. Cabrera; L. Xavier; M. D. Ferrari; C. Lareo (BioEnergy Research, 2023)

CRYSTALpytools: A Python infrastructure for the Crystal code - Bruno Camino; Huanyu Zhou; Eleonora Ascrizzi; Alberto Boccuni; Filippo Bodo; Alessandro Cossard; Davide Mitoli; Anna Maria Ferrari; Alessandro Erba; Nicholas M. Harrison (Computer Physics Communications, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Mycobacterium avium subsp. paratuberculosis and Crohn’s disease: characterization of the interaction with different aspects of the disease - I. F. Espeschit; D. S. S. Bastos; A. Fonseca Junior; S. A. Cardoso; M. L. A. Ferrari; M. A. S. Moreira (Brazilian Journal of Microbiology, 2023)

Non-toxic acid-free glyoxal fixative for veterinary histopathology, immunohistochemistry and molecular analysis - V. Zappulli; F. Torrigiani; P. Detillo; S. Iussich; M. Rondena; C. Gola; L. MInoli; E. Morello; E.I. Ferraris; A. Rigillo; B. Bussolati (Journal of Comparative Pathology, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

TMS-evoked EEG potentials demonstrate altered cortical excitability in migraine with aura - Robert M. Helling; Matthijs J. L. Perenboom; Prisca R. Bauer; Johannes A. Carpay; Josemir W. Sander; Michel D. Ferrari; Gerhard H. Visser; Else A. Tolner (Brain Topography, 2023)
Migraine is associated with altered sensory processing, that may be evident as changes in cortical responsivity due to altered excitability, especially in migraine with aura. Cortical excitability can be directly assessed by combining transcranial magnetic stimulation with electroencephalography (TMS-EEG). We measured TMS evoked potential (TEP) amplitude and response consistency as these measures have been linked to cortical excitability but were not yet reported in migraine. We recorded 64-channel EEG during single-pulse TMS on the vertex interictally in 10 people with migraine with aura and 10 healthy controls matched for age, sex and resting motor threshold. On average 160 pulses around resting motor threshold were delivered through a circular coil in clockwise and counterclockwise direction. Trial-averaged TEP responses, frequency spectra and phase clustering (over the entire scalp as well as in frontal, central and occipital midline electrode clusters) were compared between groups, including comparison to sham-stimulation evoked responses. Migraine and control groups had a similar distribution of TEP waveforms over the scalp. In migraine with aura, TEP responses showed reduced amplitude around the frontal and occipital N100 peaks. For the migraine and control groups, responses over the scalp were affected by current direction for the primary motor cortex, somatosensory cortex and sensory association areas, but not for frontal, central or occipital midline clusters. This study provides evidence of altered TEP responses in-between attacks in migraine with aura. Decreased TEP responses around the N100 peak may be indicative of reduced cortical GABA-mediated inhibition and expand observations on enhanced cortical excitability from earlier migraine studies using more indirect measurements.

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Advances in process design, techno-economic assessment and environmental aspects for hydrothermal pretreatment in the fractionation of biomass under biorefinery concept - Héctor A. Ruiz; William Gustavo Sganzerla; Valeria Larnaudie; Romy J. Veersma; Gijs van Erven; Shiva; Leopoldo J. Ríos-González; Rosa M. Rodríguez-Jasso; Gilver Rosero-Chasoy; Mario Daniel Ferrari; Mirjam A. Kabel; Tânia Forster-Carneiro; et al. (Bioresource Technology, 2023)

Nitrofurantoin-induced liver injury: long-term follow-up in two prospective DILI registries - Fernando Bessone; Antonella Ferrari; Nelia Hernandez; Manuel Mendizabal; Ezequiel Ridruejo; Alina Zerega; Federico Tanno; Maria Virginia Reggiardo; Julio Vorobioff; Hugo Tanno; Marco Arrese; Vinicius Nunes; et al. (Archives of Toxicology, 2023)
Nitrofurantoin is a synthetic antibiotic that is recommended as first-choice treatment for uncomplicated urinary tract infections. The prescription of this drug has increased dramatically, especially in Latin American countries. We described the demographics, clinical characteristics, biochemical features, and outcome of nitrofurantoin-induced liver injury. We analyzed 23 cases from the Latin American DILI Network (LATINDILI) and the Spanish DILI Registry. Causality was assessed with the RUCAM and RECAM scale. Of the 23 DILI cases included in our series, 96% patients were women, and the mean age of the whole cohort was 61 years. The median time of drug exposure was 175 days (interquartile range [IQR] 96–760), with 11 patients who were prescribed nitrofurantoin for more than six months. Hepatocellular damage was the most frequent pattern of liver injury (83%), and nearly half of the patients had an asymptomatic presentation (52%). Neither death nor liver transplantation was documented in this series. Overall, 65% of the patients ( n = 15) presented with positive autoantibody titres. The median time to resolution was 81 days (IQR 57–141), and 15 patients (83%) recovered within six months. Five patients (22%) developed nitrofurantoin-induced autoimmune-like hepatitis (NI-AILH), of whom two were characterized by a persistent increase in transaminases that required immunosuppressive treatment to achieve normalization of liver enzymes. Clinicians who prescribe nitrofurantoin should be aware that patients who had taken nitrofurantoin for a long term may be at risk of developing nitrofurantoin-induced autoimmune-like hepatitis.

An Interlaboratory Study to Identify Potential Visible Protein-Like Particle Standards - Srivalli N. Telikepalli; Michael J. Carrier; Dean C. Ripple; Greg Barnett; Ashwinkumar Bhirde; Donna Bolton; George M. Bou-Assaf; Erica Ferrari; Scott Leigh; Sophia Levitskaya-Seaman; Tim Menzen; Felix Nikels; et al. (AAPS PharmSciTech, 2022)
Visible protein-like particle standards may improve visual inspection and/or appearance testing practices used in the biotechnology industry. They may improve assay performance resulting in better alignment and more standardized training among different companies. The National Institute of Standards and Technology (NIST) has conducted an interlaboratory study to test whether the standards under development mimic typical proteinaceous particles found in biotherapeutics and if they can be implemented during the visual inspection process. Fourteen organizations from industry and government have participated. A total of 20 labs from these 14 organizations participated with analysts from 6 formulation, 7 analytical, 4 quality control, and 3 manufacturing labs. The circulated samples consisted of abraded ethylene tetrafluoroethylene (ETFE) particles or photolithographic particles. The results consist of qualitative ratings, which varied substantially among organizations and within labs. Polydisperse ETFE particle suspensions, containing particles enriched in greater than 150 µm in size, were rated more favorably than the photolithographic particles by formulation and analytical scientists. The largest monodisperse photolithographic particles (approximately 300 µm in size) were favored equally compared to ETFE by all scientists. Solution modifications to decrease the settling rate or to alter optical properties of the ETFE solutions yielded lower ratings by the analysts. Both particle types received mixed ratings for their usability and for their application for visual inspection and for training purposes. Industry feedback will assist NIST in developing reference material(s) for visible protein-like particles. Graphical Abstract

Predator-induced transgenerational plasticity in animals: a meta-analysis - Kirsty J. MacLeod; Chloé Monestier; Maud C. O. Ferrari; Katie E. McGhee; Michael J. Sheriff; Alison M. Bell (Oecologia, 2022)
There is growing evidence that the environment experienced by one generation can influence phenotypes in the next generation via transgenerational plasticity (TGP). One of the best-studied examples of TGP in animals is predator-induced transgenerational plasticity, whereby exposing parents to predation risk triggers changes in offspring phenotypes. Yet, there is a lack of general consensus synthesizing the predator–prey literature with existing theory pertaining to ecology and evolution of TGP. Here, we apply a meta-analysis to the sizable literature on predator-induced TGP (441 effect sizes from 29 species and 49 studies) to explore five hypotheses about the magnitude, form and direction of predator-induced TGP. Hypothesis #1: the strength of predator-induced TGP should vary with the number of predator cues. Hypothesis #2: the strength of predator-induced TGP should vary with reproductive mode. Hypothesis #3: the strength and direction of predator-induced TGP should vary among offspring phenotypic traits because some traits are more plastic than others. Hypothesis #4: the strength of predator-induced TGP should wane over ontogeny. Hypothesis #5: predator-induced TGP should generate adaptive phenotypes that should be more evident when offspring are themselves exposed to risk. We found strong evidence for predator-induced TGP overall, but no evidence that parental predator exposure causes offspring traits to change in a particular direction. Additionally, we found little evidence in support of any of the specific hypotheses. We infer that the failure to find consistent evidence reflects the heterogeneous nature of the phenomena, and the highly diverse experimental designs used to study it. Together, these findings set an agenda for future work in this area.

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Genome-wide association study reveals white lupin candidate gene involved in anthracnose resistance - Joris A. Alkemade; Nelson Nazzicari; Monika M. Messmer; Paolo Annicchiarico; Barbara Ferrari; Ralf T. Voegele; Maria R. Finckh; Christine Arncken; Pierre Hohmann (Theoretical and Applied Genetics, 2022)
Key message GWAS identifies candidate gene controlling resistance to anthracnose disease in white lupin. Abstract White lupin ( Lupinus albus L.) is a promising grain legume to meet the growing demand for plant-based protein. Its cultivation, however, is severely threatened by anthracnose disease caused by the fungal pathogen Colletotrichum lupini . To dissect the genetic architecture for anthracnose resistance, genotyping by sequencing was performed on white lupin accessions collected from the center of domestication and traditional cultivation regions. GBS resulted in 4611 high-quality single-nucleotide polymorphisms (SNPs) for 181 accessions, which were combined with resistance data observed under controlled conditions to perform a genome-wide association study (GWAS). Obtained disease phenotypes were shown to highly correlate with overall three-year disease assessments under Swiss field conditions ( r > 0.8). GWAS results identified two significant SNPs associated with anthracnose resistance on gene Lalb_Chr05_g0216161 encoding a RING zinc-finger E3 ubiquitin ligase which is potentially involved in plant immunity. Population analysis showed a remarkably fast linkage disequilibrium decay, weak population structure and grouping of commercial varieties with landraces, corresponding to the slow domestication history and scarcity of modern breeding efforts in white lupin. Together with 15 highly resistant accessions identified in the resistance assay, our findings show promise for further crop improvement. This study provides the basis for marker-assisted selection, genomic prediction and studies aimed at understanding anthracnose resistance mechanisms in white lupin and contributes to improving breeding programs worldwide.

Sensitivity Analysis of Single Beat Left Ventricular Elastance Estimation by Chen Method - A. Di Molfetta; G. Ferrari; V. Cusimano; G. Di Ruzza; P. Mollo; D. Boncompagni; M. Cesario; C. Volponi; M. Massetti; M. Menichelli (Cardiovascular Engineering and Technology, 2022)

The Effects of Social Factors and Kinship on Co-sleeping of Black-and-Gold Howler Monkeys (Alouatta caraya) - Melina V. Brividoro; Luciana I. Oklander; Verónica I. Cantarelli; Marina F. Ponzio; Héctor R. Ferrari; Martin M. Kowalewski (International Journal of Primatology, 2021)

The predictive capacity of the high resolution weather research and forecasting model: a year-long verification over Italy - L. Apicella; S. Puca; M. Lagasio; A. N. Meroni; M. Milelli; N. Vela; V. Garbero; L. Ferraris; A. Parodi (Bulletin of Atmospheric Science and Technology, 2021)
Numerical models are operationally used for weather forecasting activities to reduce the risks of several hydro-meteorological disasters. The overarching goal of this work is to evaluate the Weather Research and Forecasting (WRF) model predictive capabilities over the Italian national territory in the year 2018, in two specific cloud resolving configurations. The validation is carried out with a fuzzy logic approach, by comparing the precipitation predicted by the WRF model, and the precipitation observed by the national network. The fuzzy logic technique, by considering different intensity thresholds, allows to identify the reliable spatial scales of the forecasts. The same approach is applied to evaluate the performances of COSMO-2I model, a state-of-the-art numerical model configuration used for operational activities. For the entire year, except for summer, the model predictive capabilities are high, with useful forecasts for structures of medium intensities down to O (10 km) length scales. In summer the skills decrease mainly because of localization errors. The work aims to provide a robust evaluation of the forecast performances of another convection permitting operational meteorological models currently available in Italy.

Vegetation dynamics under residual large trees following a volcanic eruption in a Valdivian temperate rainforest - Lisa Hintz; Dylan Fischer; Nina Ferrari; Charles M. Crisafulli (Plant Ecology, 2021)

Exposure to degraded coral habitat depresses oxygen uptake rate during exercise of a juvenile reef fish - Adam T. Downie; Caroline M. Phelps; Rhondda Jones; Jodie L. Rummer; Douglas P. Chivers; Maud C. O. Ferrari; Mark I. McCormick (Coral Reefs, 2021)

New Horizons on Non-invasive Brain Stimulation of the Social and Affective Cerebellum - Z. Cattaneo; C. Ferrari; A. Ciricugno; E. Heleven; D. J. L. G. Schutter; M. Manto; F. Van Overwalle (The Cerebellum, 2021)

Antarctic desert soil bacteria exhibit high novel natural product potential, evaluated through long‐read genome sequencing and comparative genomics - Nicole Benaud; Richard J. Edwards; Timothy G. Amos; Paul M. D'Agostino; Carolina Gutiérrez‐Chávez; Kate Montgomery; Iskra Nicetic; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Actinobacteria and Proteobacteria are important producers of bioactive natural products (NP), and these phyla dominate in the arid soils of Antarctica, where metabolic adaptations influence survival under harsh conditions. Biosynthetic gene clusters (BGCs) which encode NPs, are typically long and repetitious high G + C regions difficult to sequence with short‐read technologies. We sequenced 17 Antarctic soil bacteria from multi‐genome libraries, employing the long‐read PacBio platform, to optimize capture of BGCs and to facilitate a comprehensive analysis of their NP capacity. We report 13 complete bacterial genomes of high quality and contiguity, representing 10 different cold‐adapted genera including novel species. Antarctic BGCs exhibited low similarity to known compound BGCs (av. 31%), with an abundance of terpene, non‐ribosomal peptide and polyketide‐encoding clusters. Comparative genome analysis was used to map BGC variation between closely related strains from geographically distant environments. Results showed the greatest biosynthetic differences to be in a psychrotolerant Streptomyces strain, as well as a rare Actinobacteria genus, Kribbella , while two other Streptomyces spp. were surprisingly similar to known genomes. Streptomyces and Kribbella BGCs were predicted to encode antitumour, antifungal, antibacterial and biosurfactant‐like compounds, and the synthesis of NPs with antibacterial, antifungal and surfactant properties was confirmed through bioactivity assays.

Relative Abundance of Floating Plastic Debris and Neuston in the Eastern North Pacific Ocean - Matthias Egger; Lauren Quiros; Giulia Leone; Francesco Ferrari; Christiana M. Boerger; Michelle Tishler (Frontiers in Marine Science, 2021)
Despite an increasing research conducted on ocean plastic pollution over the last decade, there are still large knowledge gaps in our current understanding of how floating plastic debris accumulating in subtropical oceanic gyres may harm the surface-associated pelagic community known as neuston. Removing floating plastic debris from the surface ocean can minimize potentially adverse effects of plastic pollution on the neuston, as well as prevent the formation of large quantities of secondary micro- and nanoplastics. However, due to the scarcity of observational data from remote and difficult to access offshore waters, neuston dynamics in subtropical oceanic gyres and thus the potential impacts of plastic pollution as well as of cleanup activities on the neuston remain uncertain. Here, we provide rare observational data of the relative distribution of floating plastic debris (0.05–5 cm in size) and members of the neuston in the eastern North Pacific Ocean. Our results reveal that the dominant neustonic species co-occurring with high concentrations of floating plastic debris in the North Pacific Garbage Patch (NPGP) such as Porpita porpita , Halobates spp., pteropods, isopods, heteropods, and crabs depict either a low atmospheric drag due to physical attributes or a potential plastic-associated fitness benefit such as increased surface area for oviposition and structure for habitat. We further observe relatively higher plastic to organism ratios inside the NPGP for most target species compared to waters outside the NPGP. The findings presented here provide a first observational baseline to develop ecological models that can help evaluate the long-term risks of plastic pollution and of offshore cleanup activities for neuston in the eastern North Pacific Ocean. We further suggest that offshore mitigation strategies aiming at removing floating plastic debris from the ocean surface need to evaluate both, the direct impact of neuston bycatch during plastic removal on neuston population dynamics, as well as the potential benefits of reducing the negative effects of plastic pollution on the neuston.

Interferon-γ Involvement in the Neuroinflammation Associated with Parkinson’s Disease and L-DOPA-Induced Dyskinesia - D. P. Ferrari; M. Bortolanza; E. A. Del Bel (Neurotoxicity Research, 2021)

Physical activity for cancer patients during COVID-19 pandemic: a call to action - Leandro F. M. Rezende; Dong Hoon Lee; Gerson Ferrari; José Eluf-Neto; Edward L. Giovannucci (Cancer Causes & Control, 2021)

Organic carbon accumulation and productivity over the past 130 years in Lake Kawaguchi (central Japan) reconstructed using organic geochemical proxies - Shinya Yamamoto; Aurélia Hubert-Ferrari; Laura Lamair; Yoshiki Miyata; Shinya Ochiai; Seiya Nagao; Nobuo Miyauchi; Kunio Yoshida; Osamu Fujiwara; Yusuke Yokoyama; Vanessa M. A. Heyvaert; Marc De Batist; et al. (Journal of Paleolimnology, 2020)

IL-33 enhances macrophage release of IL-1β and promotes pain and inflammation in gouty arthritis - Victor Fattori; Larissa Staurengo-Ferrari; Tiago H. Zaninelli; Rubia Casagrande; Rene D. Oliveira; Paulo Louzada-Junior; Thiago M. Cunha; Jose C. Alves-Filho; Mauro M. Teixeira; Fernando Q. Cunha; Flavio A. Amaral; Waldiceu A. Verri (Inflammation Research, 2020)

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Seismological analyses of the seismic microzonation of 138 municipalities damaged by the 2016–2017 seismic sequence in Central Italy - E. Priolo; F. Pacor; D. Spallarossa; G. Milana; G. Laurenzano; M. A. Romano; C. Felicetta; S. Hailemikael; F. Cara; G. Di Giulio; G. Ferretti; C. Barnaba; et al. (Bulletin of Earthquake Engineering, 2020)
This paper describes the seismological analyses performed within the framework of the seismic microzonation study for the reconstruction of 138 municipalities damaged by the 2016–2017 sequence in Central Italy. Many waveforms were recorded over approximately 15 years at approximately 180 instrumented sites equipped with permanent or temporary stations in an area that includes all the damaged localities. Site response was assessed using earthquake and noise recordings at the selected stations through different parameters, such as spectral amplification curves, fundamental resonance frequencies, site-specific response spectra, and average amplification factors. The present study was a collaboration of many different institutions under the coordination of the Italian Center for Seismic Microzonation and its applications . The results were homogenized and gathered into site-specific forms, which represent the main deliverable for the benefit of Italian Civil Protection. It is remarkable that the bulk of this study was performed in a very short period (approximately 2 months) to provide quantitative information for detailed microzonation and future reconstruction of the damaged municipalities.

Cellular and molecular effects of silymarin on the transdifferentiation processes of LX-2 cells and its connection with lipid metabolism - Caio Mateus Silva; Gustavo Duarte Ferrari; Luciane Carla Alberici; Osmar Malaspina; Karen C. M. Moraes (Molecular and Cellular Biochemistry, 2020)

Type three secretion system in Salmonella Typhimurium: the key to infection - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Genes & Genomics, 2020)

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Comparative diversity of anemone-associated fishes and decapod crustaceans in a Belizean coral reef and seagrass system - Rohan M. Brooker; William E. Feeney; Tiffany L. Sih; Maud. C. O. Ferrari; Douglas P. Chivers (Marine Biodiversity, 2019)

Does Sugarcane Straw Removal Change the Abundance of Soil Microbes? - Maristela C. Morais; Beatriz M. Ferrari; Clovis D. Borges; Maurício R. Cherubin; Siu Mui Tsai; Carlos C. Cerri; Carlos E. P. Cerri; Brigitte J. Feigl (BioEnergy Research, 2019)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Evaluating adaptive, carry‐over, and plastic antipredator responses across a temporal gradient in Pacific chorus frogs - Tiffany S. Garcia; Evan M. Bredeweg; Jenny Urbina; Maud C. O. Ferrari (Ecology, 2019)
The development of antipredator traits is dependent on the frequency and intensity of predator exposure over evolutionary and ecological time. We hypothesized that prey species would respond with increasing accuracy when exposed to predators across generational, ontogenetic, and immediate time scales. We assessed larval Pacific chorus frog ( PSRE ; Pseudacris regilla ) individuals that varied in population sympatry, embryonic conditioning, and immediate exposure to stocked populations of rainbow trout ( Oncorhynchus mykiss ). Using PSRE populations from sites with and without resident rainbow trout, we conditioned embryos to trout odor, PSRE alarm cues, trout odor in combination with alarm cues, or control water. After being hatched and reared in control water, individuals were exposed to the four predator cue treatments using a fully factorial design. Tadpoles from populations with resident rainbow trout did not behave or develop differently than tadpoles originating from fishless sites. However, we found evidence that PSRE reduced predation risk with a combination of carry‐over effect (i.e., transfer of information across life history stages) and within‐life stage phenotypically plastic mechanisms. We found both developmental and behavioral carry‐over effects: tadpoles conditioned with trout odor as embryos grew more slowly and took refuge more often than control animals. Within‐life‐stage behavioral plasticity was observed in tadpoles from all treatment groups, responding to predator cues with increased refuge use. Potentially additive effects of predator exposure on prey response should be considered when predicting the ability of prey to recognize novel threats.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Survival, behaviour, and morphology of larval wood frogs, Lithobates sylvaticus, under threat from an exotic crayfish predator, Orconectes virilis - Adam L. Crane; Kevin R. Bairos-Novak; Dale M. Jefferson; Douglas P. Chivers; Maud C. O. Ferrari (Aquatic Ecology, 2019)

Stereotactic radiation therapy in oligometastatic colorectal cancer: outcome of 102 patients and 150 lesions - V. Dell’Acqua; A. Surgo; F. Kraja; J. Kobiela; Maria Alessia Zerella; P. Spychalski; S. Gandini; C. M. Francia; D. Ciardo; C. Fodor; A. M. Ferrari; G. Piperno; et al. (Clinical & Experimental Metastasis, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Diallelic Analysis of Endogamic Maize Lines with Emphasis on Agronomic Traits of Tassel in Different Environments - D. Barreta; M. Nardino; V. A. Konflanz; A. J. de Pelegrin; M. Ferrari; V. J. Szareski; I. R. Carvalho; V. Q. de Souza; A. C. de Oliveira; L. C. da Maia (Journal of Crop Science and Biotechnology, 2019)

Virulence Factors in Salmonella Typhimurium: The Sagacity of a Bacterium - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Current Microbiology, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

Who’s where? Ecological uncertainty shapes neophobic predator avoidance in Trinidadian guppies - Laurence E. A. Feyten; Ebony E. E. M. Demers; Indar W. Ramnarine; Douglas P. Chivers; Maud C. O. Ferrari; Grant E. Brown (Behavioral Ecology and Sociobiology, 2019)

Reversed Auxiliary Flow to Reduce Embolism Risk During TAVI: A Computational Simulation and Experimental Study - Michele Conti; Stijn Vandenberghe; Stefania Marconi; Enrico Ferrari; Rodrigo M. Romarowski; Simone Morganti; Ferdinando Auricchio; Stefanos Demertzis (Cardiovascular Engineering and Technology, 2019)

Mild Exercise Differently Affects Proteostasis and Oxidative Stress on Motor Areas During Neurodegeneration: A Comparative Study of Three Treadmill Running Protocols - Karla P. Melo; Carolliny M. Silva; Michael F. Almeida; Rodrigo S. Chaves; Tania Marcourakis; Sandra M. Cardoso; Marilene Demasi; Luis E. S. Netto; Merari F. R. Ferrari (Neurotoxicity Research, 2019)

Chronic Hippocampal Expression of Notch Intracellular Domain Induces Vascular Thickening, Reduces Glucose Availability, and Exacerbates Spatial Memory Deficits in a Rat Model of Early Alzheimer - Pablo Galeano; María C. Leal; Carina C. Ferrari; María C. Dalmasso; Pamela V. Martino Adami; María I. Farías; Juan C. Casabona; Mariana Puntel; Sonia Do Carmo; Clara Smal; Martín Arán; Eduardo M. Castaño; et al. (Molecular Neurobiology, 2018)

Impact of the Use of a Teaching Toolbox in an Awareness Campaign on Children's Representations of Coral Reefs - Pascale Chabanet; Georgeta Stoica; Stéphanie M. Carrière; Catherine Sabinot; Claire Bedrossian; Jocelyne Ferraris (Frontiers in Marine Science, 2018)

Marine infrastructure supports abundant, diverse fish assemblages at the expense of beta diversity - A. G. Porter; R. L. Ferrari; B. P. Kelaher; S. D. A. Smith; R. A. Coleman; M. Byrne; W. Figueira (Marine Biology, 2018)

Nucleolar activity in Triticum x Thinopyrum hybrids with different ploidy level - M. Fradkin; E. J. Greizerstein; M. R. Ferrari; L. Poggio (Plant Biosystems, 2017)

Diversity in a pea (Pisum sativum) world collection for key agronomic traits in a rain-fed environment of Southern Europe - P. Annicchiarico; M. Romani; G. Cabassi; B. Ferrari (Euphytica, 2017)

Cadmium effects on some energy metabolism variables in Cnesterodon decemmaculatus adults - Federico G. Baudou; Natalia A. Ossana; Patricia M. Castañé; Martina M. Mastrángelo; Lucrecia Ferrari (Ecotoxicology, 2017)

Quercetin inhibits gout arthritis in mice: induction of an opioid-dependent regulation of inflammasome - Kenji W. Ruiz-Miyazawa; Larissa Staurengo-Ferrari; Sandra S. Mizokami; Talita P. Domiciano; Fabiana T. M. C. Vicentini; Doumit Camilios-Neto; Wander R. Pavanelli; Phileno Pinge-Filho; Flávio A. Amaral; Mauro M. Teixeira; Rubia Casagrande; Waldiceu A. Verri (Inflammopharmacology, 2017)

Embryonic learning and developmental carry-over effects in an invasive anuran - Tiffany S. Garcia; Jenny C. Urbina; Evan M. Bredeweg; Maud C. O. Ferrari (Oecologia, 2017)

Probucol attenuates overt pain-like behavior and carrageenan-induced inflammatory hyperalgesia and leukocyte recruitment by inhibiting NF-кB activation and cytokine production without antioxidant effects - Amanda Z. Zucoloto; Marília F. Manchope; Larrisa Staurengo-Ferrari; José C. Alves-Filho; Thiago M. Cunha; Maísa M. Antunes; Gustavo B. Menezes; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammation Research, 2017)

Cortical Spreading Depression Causes Unique Dysregulation of Inflammatory Pathways in a Transgenic Mouse Model of Migraine - Else Eising; Reinald Shyti; Peter A. C. ’t Hoen; Lisanne S. Vijfhuizen; Sjoerd M. H. Huisman; Ludo A. M. Broos; Ahmed Mahfouz; Marcel J. T. Reinders; Michel D. Ferrari; Else A. Tolner; Boukje de Vries; Arn M. J. M. van den Maagdenberg (Molecular Neurobiology, 2017)

Solar photocatalytic degradation of textile effluent with TiO2, ZnO, and Nb2O5 catalysts: assessment of photocatalytic activity and mineralization - Renata P. Souza; Elizangela Ambrosio; Maisa T. F. Souza; Thábata K. F. S. Freitas; Ana M. Ferrari-Lima; Juliana C. Garcia (Environmental Science and Pollution Research, 2017)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

Impairment of mitochondria dynamics by human A53T α-synuclein and rescue by NAP (davunetide) in a cell model for Parkinson’s disease - T. Q. Melo; K. C. van Zomeren; M. F. R. Ferrari; H. W. G. M. Boddeke; J. C. V. M. Copray (Experimental Brain Research, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Habitat degradation disrupts neophobia in juvenile coral reef fish - Mark I. McCormick; Douglas P. Chivers; Bridie J. M. Allan; Maud C. O. Ferrari (Global Change Biology, 2017)
Habitat degradation not only disrupts habitat‐forming species, but alters the sensory landscape within which most species must balance behavioural activities against predation risk. Rapidly developing a cautious behavioural phenotype, a condition known as neophobia, is advantageous when entering a novel risky habitat. Many aquatic organisms rely on damage‐released conspecific cues (i.e. alarm cues) as an indicator of impending danger and use them to assess general risk and develop neophobia. This study tested whether settlement‐stage damselfish associated with degraded coral reef habitats were able to use alarm cues as an indicator of risk and, in turn, develop a neophobic response at the end of their larval phase. Our results indicate that fish in live coral habitats that were exposed to alarm cues developed neophobia, and, in situ , were found to be more cautious, more closely associated with their coral shelters and survived four‐times better than non‐neophobic control fish. In contrast, fish that settled onto degraded coral habitats did not exhibit neophobia and consequently suffered much greater mortality on the reef, regardless of their history of exposure to alarm cues. Our results show that habitat degradation alters the efficacy of alarm cues with phenotypic and survival consequences for newly settled recruits.

Targeted re‐sequencing confirms the importance of chemosensory genes in aphid host race differentiation - Isobel Eyres; Ludovic Duvaux; Karim Gharbi; Rachel Tucker; David Hopkins; Jean‐Christophe Simon; Julia Ferrari; Carole M. Smadja; Roger K. Butlin (Molecular Ecology, 2017)
Host‐associated races of phytophagous insects provide a model for understanding how adaptation to a new environment can lead to reproductive isolation and speciation, ultimately enabling us to connect barriers to gene flow to adaptive causes of divergence. The pea aphid ( Acyrthosiphon pisum) comprises host races specializing on legume species and provides a unique system for examining the early stages of diversification along a gradient of genetic and associated adaptive divergence. As host choice produces assortative mating, understanding the underlying mechanisms of choice will contribute directly to understanding of speciation. As host choice in the pea aphid is likely mediated by smell and taste, we use capture sequencing and SNP genotyping to test for the role of chemosensory genes in the divergence between eight host plant species across the continuum of differentiation and sampled at multiple locations across western Europe. We show high differentiation of chemosensory loci relative to control loci in a broad set of pea aphid races and localities, using a model‐free approach based on principal component analysis. Olfactory and gustatory receptors form the majority of highly differentiated genes and include loci that were already identified as outliers in a previous study focusing on the three most closely related host races. Consistent indications that chemosensory genes may be good candidates for local adaptation and barriers to gene flow in the pea aphid open the way to further investigations aiming to understand their impact on gene flow and to determine their precise functions in response to host plant metabolites.

Protective activity of an anthocyanin-rich extract from bilberries and blackcurrants on acute acetaminophen-induced hepatotoxicity in rats - M. Cristani; A. Speciale; F. Mancari; T. Arcoraci; D. Ferrari; D. Fratantonio; A. Saija; F. Cimino; D. Trombetta (Natural Product Research, 2016)

Polymorphisms of dopamine receptor genes and risk of visual hallucinations in Parkinson’s patients - M Ferrari; C Comi; F Marino; L Magistrelli; F De Marchi; R Cantello; G Riboldazzi; G Bono; M Cosentino (European Journal of Clinical Pharmacology, 2016)

”LOVE TO HATE” pesticides: felicity or curse for the soil microbial community? An FP7 IAPP Marie Curie project aiming to establish tools for the assessment of the mechanisms controlling the interactions of pesticides with soil microorganisms - D. G. Karpouzas; G. Tsiamis; M. Trevisan; F. Ferrari; C. Malandain; O. Sibourg; F. Martin-Laurent (Environmental Science and Pollution Research, 2016)

Differential gene expression according to race and host plant in the pea aphid - Isobel Eyres; Julie Jaquiéry; Akiko Sugio; Ludovic Duvaux; Karim Gharbi; Jing‐Jiang Zhou; Fabrice Legeai; Michaela Nelson; Jean‐Christophe Simon; Carole M. Smadja; Roger Butlin; Julia Ferrari (Molecular Ecology, 2016)
Host‐race formation in phytophagous insects is thought to provide the opportunity for local adaptation and subsequent ecological speciation. Studying gene expression differences amongst host races may help to identify phenotypes under (or resulting from) divergent selection and their genetic, molecular and physiological bases. The pea aphid ( Acyrthosiphon pisum ) comprises host races specializing on numerous plants in the Fabaceae and provides a unique system for examining the early stages of diversification along a gradient of genetic and associated adaptive divergence. In this study, we examine transcriptome‐wide gene expression both in response to environment and across pea aphid races selected to cover the range of genetic divergence reported in this species complex. We identify changes in expression in response to host plant, indicating the importance of gene expression in aphid–plant interactions. Races can be distinguished on the basis of gene expression, and higher numbers of differentially expressed genes are apparent between more divergent races; these expression differences between host races may result from genetic drift and reproductive isolation and possibly divergent selection. Expression differences related to plant adaptation include a subset of chemosensory and salivary genes. Genes showing expression changes in response to host plant do not make up a large portion of between‐race expression differences, providing confirmation of previous studies’ findings that genes involved in expression differences between diverging populations or species are not necessarily those showing initial plasticity in the face of environmental change.

Pyrrolidine dithiocarbamate inhibits superoxide anion-induced pain and inflammation in the paw skin and spinal cord by targeting NF-κB and oxidative stress - Felipe A. Pinho-Ribeiro; Victor Fattori; Ana C. Zarpelon; Sergio M. Borghi; Larissa Staurengo-Ferrari; Thacyana T. Carvalho; Jose C. Alves-Filho; Fernando Q. Cunha; Thiago M. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammopharmacology, 2016)

Genetic introgression of hybrid Rhododendron x intermedium Tausch is habitat mediated: Evidences from south-eastern Alps (Italy) - I. Bruni; F. De Mattia; S. Fluch; C. Ferrari; M. Corazza; E. Dinelli; M. Labra (Plant Biosystems, 2016)

Gene co-expression analysis identifies brain regions and cell types involved in migraine pathophysiology: a GWAS-based study using the Allen Human Brain Atlas - Else Eising; Sjoerd M. H. Huisman; Ahmed Mahfouz; Lisanne S. Vijfhuizen; Verneri Anttila; Bendik S. Winsvold; Tobias Kurth; M. Arfan Ikram; Tobias Freilinger; Jaakko Kaprio; Dorret I. Boomsma; Cornelia M. van Duijn; et al. (Human Genetics, 2016)

Insect life history and the evolution of bacterial mutualism - Lee M. Henry; Martin C. J. Maiden; Julia Ferrari; H. Charles J. Godfray (Ecology Letters, 2015)
Bacterial symbiosis has played a fundamental role in the evolution of eukaryotes. However, we still know little about how cooperative relationships with bacteria originate, and why they form in some host species but not others. Facultative symbionts that are beneficial, but not essential, provide unique insights into these processes. We use data from over a hundred aphid species to test if host life history is associated with the presence of facultative symbionts. We find that aphid species that have mutualistic associations with ants that protect them from natural enemies are less likely to carry symbionts that provide similar benefits. We also find one symbiont species occurs more frequently in unrelated aphid species that specialise on certain plant genera. In addition, aphid species that attack multiple plants often carry different symbiont complements. Our findings provide evidence of the ecological conditions that facilitate stable, mutually beneficial relationships between microbes and eukaryotic hosts.

The effects of maternal immunity and age structure on population immunity to measles - A. McKee; M. J. Ferrari; K. Shea (Theoretical Ecology, 2015)
Measles was successfully eradicated in the Pan-American Health Region in 2002. However, maintenance of elimination in parts of Africa, Europe, the USA, and other regions is proving difficult, despite apparently high vaccine coverage. This may be due to the different age structure in developed and developing populations, as well as to differences in the duration of maternal immunity. We explore the interaction between maternal immunity and age structure and quantify the resulting immunity gap between vaccine coverage and population immunity; we use this immunity gap as a novel metric of vaccine program success as it highlights the difference between actual and estimated immunity. We find that, for some combinations of maternal immunity and age structure, the accepted herd immunity threshold is not maintainable with a single-dose vaccine strategy for any combination of target age and coverage. In all cases, the herd immunity threshold is more difficult to maintain in a population with developing age structure. True population immunity is always improved if the target age at vaccination is chosen for the specific combination of maternal immunity and age structure.

A unifying gravity framework for dispersal - Eelke Jongejans; Olav Skarpaas; Matthew J. Ferrari; Eric S. Long; Joseph T. Dauer; Carrie M. Schwarz; Emily S. J. Rauschert; Randa Jabbour; David A. Mortensen; Scott A. Isard; David A. Lieb; Zeynep Sezen; et al. (Theoretical Ecology, 2015)

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

Seismicity of Northwestern Italy during the last 30 years - D. Scafidi; S. Barani; R. De Ferrari; G. Ferretti; M. Pasta; M. Pavan; D. Spallarossa; C. Turino (Journal of Seismology, 2015)

The ruthenium nitric oxide donor, [Ru(HEDTA)NO], inhibits acute nociception in mice by modulating oxidative stress, cytokine production and activating the cGMP/PKG/ATP-sensitive potassium channel signaling pathway - Larissa Staurengo-Ferrari; Sandra S. Mizokami; Victor Fattori; Jean J. Silva; Patrícia G. Zanichelli; Sandra R. Georgetti; Marcela M. Baracat; Luiz G. da França; Wander R. Pavanelli; Rubia Casagrande; Waldiceu A. Verri (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Social learning of predators by coral reef fish: does observer number influence acquisition of information? - R. P. Manassa; M. I. McCormick; D. L. Dixson; M. C. O. Ferrari; D. P. Chivers (Behavioral Ecology and Sociobiology, 2014)

The Effects of Chronic Exposure to Environmentally Relevant Levels of Waterborne Cadmium on Reproductive Capacity and Behaviour in Fathead Minnows - Yinxian Wang; Maud C. O. Ferrari; Zachary Hoover; Ali M. Yousafzai; Douglas P. Chivers; Som Niyogi (Archives of Environmental Contamination and Toxicology, 2014)

Bronchial microbiome of severe COPD patients colonised by Pseudomonas aeruginosa - L. Millares; R. Ferrari; M. Gallego; M. Garcia-Nuñez; V. Pérez-Brocal; M. Espasa; X. Pomares; C. Monton; A. Moya; E. Monsó (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Frugal cannibals: how consuming conspecific tissues can provide conditional benefits to wood frog tadpoles (Lithobates sylvaticus) - Dale M. Jefferson; Keith A. Hobson; Brandon S. Demuth; Maud C. O. Ferrari; Douglas P. Chivers (The Science of Nature, 2014)

Biodegradation of ballast tank coating investigated by impedance spectroscopy and microscopy - A. Heyer; F. D’Souza; X. Zhang; G. Ferrari; J. M. C. Mol; J. H. W. de Wit (Biodegradation, 2014)

Spatial models to support the management of coastal marine ecosystems: a short review of the best practices in Liguria, Italy - M. VACCHI; M. MONTEFALCONE; V. PARRAVICINI; A. ROVERE; P. VASSALLO; M. FERRARI; C. MORRI; C. N. BIANCHI (Mediterranean Marine Science, 2013)
Spatial modelling is an emerging approach to the management of coastal marine habitats, as it helps understanding and predicting the results of global change. This paper reviews critically two recent examples developed in Liguria, an administrative region of NW Italy. The first example, aiming at predicting habitat status depending on pressures, provides managers with the opportunity of envisaging different scenarios for the consequences of coastal development choices. The second example defines the status of an important Mediterranean coastal marine habitat (Posidonia oceanica meadows) under natural conditions, allowing for quantifying human impacts on regressed meadows. Both modelling approaches are useful to define the targets of coastal management, and may help choosing the best management option. Well-planned and sustained monitoring is essential to model validation and improvement.

Investigating the feasibility of using DNA from sloughed skin for individual identification and kinship analysis in humpback whales ( Megaptera novaeangliae ) - S. P. Pierszalowski; M. Ferrari; D. Glockner‐Ferrari; S. Mizroch; P. J. Clapham; B. R. Dickerson (Marine Mammal Science, 2013)

From repulsion to attraction: species- and spatial context-dependent threat sensitive response of the spider mite Tetranychus urticae to predatory mite cues - M. Celeste Fernández Ferrari; Peter Schausberger (The Science of Nature, 2013)

Retention of acquired predator recognition among shy versus bold juvenile rainbow trout - G. E. Brown; M. C. O. Ferrari; P. H. Malka; L. Fregeau; L. Kayello; D. P. Chivers (Behavioral Ecology and Sociobiology, 2013)

Do fathead minnows, Pimephales promelas Rafinesque, alter their club cell investment in responses to variable risk of infection from Saprolegnia ? - R J Pollock; M S Pollock; M C O Ferrari; S G W Kaminskyj; D P Chivers (Journal of Fish Diseases, 2012)
Fish in the Superorder Ostariophysi possess large epidermal club cells that release chemical cues warning nearby conspecifics of danger. Despite the long‐held assumption that such club cells evolved under the selective force of predation, recent studies demonstrated that predation has no effect on club cell investment. Rather, club cells have an immune function and cell production may be stimulated by skin‐penetrating pathogens and parasites. The current work investigates whether fathead minnows, Pimephales promelas , alter their club cell characteristics based on variation in infection risk. In a 2 × 3 design, we exposed minnows to infective cysts of two oomycete species ( Saprolegnia ferax and S. parasitica ) at three different concentrations (2, 20 or 200 cysts L −1 ). Club cell characteristics (number and size) were quantified 12 days after exposure. Saprolegnia parasitica is thought to be more pathogenic than S. ferax , hence we predicted greater club cell investment and a larger turnover rate of cells by minnows exposed to S. parasitica than S. ferax. We also predicted that minnows exposed to higher numbers of cysts should invest more in club cells and have a higher turnover rate of cells. We found no difference in club cell density or size between fish exposed to the two Saprolegnia species; however, fish exposed to high concentrations of pathogens had smaller club cells than those exposed to low concentrations, indicating a higher rate of turnover of cells in the epidermis.

Influence of air pressure, humidity, solar radiation, temperature, and wind speed on ambulatory visits due to chronic obstructive pulmonary disease in Bavaria, Germany - Uta Ferrari; Teresa Exner; Eva R Wanka; Christoph Bergemann; Julian Meyer-Arnek; Beate Hildenbrand; Amanda Tufman; Christian Heumann; Rudolf M Huber; Michael Bittner; Rainald Fischer (International Journal of Biometeorology, 2012)

Levels of copper in Nile tilapia from Brazil - Renato C.F. Neves; Paula M. Moraes; Jeisson E.M. Ferrari; Paula M. Lima; Felipe A. Santos; Gustavo Rocha de Castro; Margarida M. Barros; Pedro M. Padilha (Food Additives & Contaminants Part B-Surveillance, 2011)

Methodological characteristics of the national dietary surveys carried out in the European Union as included in the European Food Safety Authority (EFSA) Comprehensive European Food Consumption Database - C. Merten; P. Ferrari; M. Bakker; A. Boss; Á. Hearty; C. Leclercq; O. Lindtner; C. Tlustos; P. Verger; J.L. Volatier; D. Arcella (Food Additives & Contaminants: Part A, 2011)

Intake of aflatoxins through the consumption of peanut products in Brazil - I.C.O. Magrine; S.S.C. Ferrari; G.F. Souza; L. Minamihara; C. Kemmelmeier; E. Bando; M. Machinski (Food Additives & Contaminants Part B-Surveillance, 2011)

Plasticity of Opioid Receptors in the Female Periaqueductal Gray: Multiparity-Induced Increase in the Activity of Genes Encoding for Mu and Kappa Receptors and a Post-Translational Decrease in Delta Receptor Expression - Elizabeth Teodorov; Maria M. Bernardi; Merari F. R. Ferrari; Debora R. Fior-Chadi; Luciano F. Felicio (Journal of Molecular Neuroscience, 2011)

Long‐term survival of humpback whales radio‐tagged in Alaska from 1976 through 1978 - Sally A. Mizroch; Michael F. Tillman; Susan Jurasz; Janice M. Straley; Olga Von Ziegesar; Louis M. Herman; Adam A. Pack; Scott Baker; Jim Darling; Debbie Glockner‐Ferrari; Mark Ferrari; Dan R. Salden; et al. (Marine Mammal Science, 2011)
Invasive tags designed to provide information on animal movements through radio or satellite monitoring have tremendous potential for the study of whales and other cetaceans. However, to date there have been no published studies on the survival of tagged animals over periods of years or decades. Researchers from the National Marine Mammal Laboratory and the Woods Hole Oceanographic Institution tracked five humpback whales with implanted radio tags in southeastern Alaska in August 1976 and July 1977, and tracked two humpback whales in Prince William Sound, Alaska, in June 1978. All seven of these individually identified humpback whales were resighted at least 20 yr after first being tagged, and five of the seven have been observed for more than 30 yr; some of them are among the most resighted humpback whales in the North Pacific. Photos of tagging sites taken during and subsequent to tagging operations show persistent but superficial scarring and no indication of infection. These pioneering field studies demonstrated both long‐term survival of the whales and the short‐term effects of deploying radio tags, which at the time were larger and more invasive than those typically used today.

Design and preparation of market baskets of European Union commercial baby foods for the assessment of infant exposure to food chemicals and to their effects - R. Piccinelli; M. Pandelova; C. Le Donne; M. Ferrari; K.-W. Schramm; C. Leclercq (Food Additives & Contaminants: Part A, 2010)

Use of a comprehensive numerical model to improve biventricular pacemaker temporization in patients affected by heart failure undergoing to CRT-D therapy - A. Di Molfetta; L. Santini; G. B. Forleo; M. Cesario; C. Tota; M. Sgueglia; D. Sergi; G. Ferrari; F. Romeo (Medical & Biological Engineering & Computing, 2010)

Anti N1 Cross-Protecting Antibodies Against H5N1 Detected in H1N1 Infected People - E. Frobert; M. Bouscambert-Duchamp; V. Escuret; S. Mundweiler; M. Barthélémy; F. Morfin; M. Valette; C. Gerdil; B. Lina; O. Ferraris (Current Microbiology, 2010)

Chronic variable stress impairs energy metabolism in prefrontal cortex and hippocampus of rats: prevention by chronic antioxidant treatment - Bárbara Tagliari; Cristie G. Noschang; Andréia G. K. Ferreira; Otávio A. Ferrari; Luciane R. Feksa; Clovis M. D. Wannmacher; Carla Dalmaz; Angela T. S. Wyse (Metabolic Brain Disease, 2010)

Copper (II) adsorption studies using models of synthetic humic acids - Marcilene Ferrari Barriquello; N. Consolin-Filho; E. R. Carvalho; M. Y. Kamogawa; L. Martin-Neto (Environmental Chemistry Letters, 2010)

Records of large earthquakes in lake sediments along the North Anatolian Fault, Turkey - X. Boës; S. B. Moran; J. King; M. N. Cağatay; A. Hubert-Ferrari (Journal of Paleolimnology, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Microbial sequences retrieved from environmental samples from seasonal Arctic snow and meltwater from Svalbard, Norway - Catherine Larose; Sibel Berger; Christophe Ferrari; Elisabeth Navarro; Aurélien Dommergue; Dominique Schneider; Timothy M. Vogel (Extremophiles, 2010)

Detection of porcine circovirus type 2 (PCV2) from wild boars in central Italy - S. Petrini; S. Barocci; S. Gavaudan; R. Villa; S. Briscolini; M. Sabbatini; C. Mattozzi; F. Barchiesi; S. Salamida; M. Ferrari; M. Paniccià; G. Pezzotti (European Journal of Wildlife Research, 2009)

Cellular immune response and immunotoxicity induced by DON (deoxynivalenol) in piglets - L. Ferrari; A. M. Cantoni; P. Borghetti; E. De Angelis; A. Corradi (Veterinary Research Communications, 2009)

Social context, competitive interactions and the dynamic nature of antipredator responses of juvenile rainbow trout Oncorhynchus mykiss - G. E. Brown; M. C. Harvey; A. O. H. C. Leduc; M. C. O. Ferrari; D. P. Chivers (Journal of Fish Biology, 2009)
The effects of food ration and social context, as well as possible interactions, on the antipredator behaviour of juvenile rainbow trout Onchorhynchus mykiss were investigated in a pair of laboratory studies. In experiment 1, pairs of dominant and subordinate O. mykiss were exposed to conspecific alarm cues when maintained under high or low food rations. Under high food rations, dominant individuals responded to predation risk, whereas subordinates used the opportunity to feed. Under low food ration, however, the opposite pattern was observed, where subordinates responded to predation cues and dominants did not. Experiment 2 consisted of performing the same experiment, however separating the dominant and subordinate O. mykiss 3 h before testing. When tested separately, dominant and subordinate individuals did not differ in their responses to alarm cues, regardless of food ration. These results demonstrate that there is a complex interaction between current energy status and social context on decision making by prey animals.

Molecular genetics of migraine - Boukje de Vries; Rune R. Frants; Michel D. Ferrari; Arn M. J. M. van den Maagdenberg (Human Genetics, 2009)

Abnormal meiosis in tetraploid genotypes ofBrachiaria brizantha (Poaceae) induced by colchicine: its implications for breeding - A. B. Mendes-Bonato; M. Ferrari Felismino; A. M. Souza Kaneshima; C. Pessim; V. Calisto; M. Suely Pagliarini; C. Borges do Valle (Journal of Applied Genetics, 2009)

Applications of flow cytometry in environmental microbiology and biotechnology - Peter L. Bergquist; Elizabeth M. Hardiman; Belinda C. Ferrari; Tristrom Winsley (Extremophiles, 2009)

Habitat Exploitation by Free-ranging Saguinus niger in Eastern Amazonia - Ana Cristina M. Oliveira; Stephen F. Ferrari (International Journal of Primatology, 2008)

A comparison of the humoral and cell-mediated response of pigs experimentally infected with either influenza or PRRS viruses - M. Ferrari; P. Candotti; G. Lombardi; M. Amadori; S. Dotti; S. Guana; S. Petrini (Veterinary Research Communications, 2008)

The effect of acute hypoxia on swimming stamina at optimal swimming speed in flathead grey mullet Mugil cephalus - M. Vagner; C. Lefrançois; R. S. Ferrari; A. Satta; P. Domenici (Marine Biology, 2008)

Saliva as an analytical tool to measure occupational exposure to toluene - M. Ferrari; S. Negri; P. Zadra; S. Ghittori; M. Imbriani (International Archives of Occupational and Environmental Health, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Quaternary adakite—Nb-enriched basalt association in the western Trans-Mexican Volcanic Belt: is there any slab melt evidence? - Chiara M. Petrone; Luca Ferrari (Contributions to Mineralogy and Petrology, 2008)

Closed-tube DNA extraction using a thermostable proteinase is highly sensitive, capable of single parasite detection - B. C. Ferrari; M. L. Power; P. L. Bergquist (Biotechnology Letters, 2007)

Adult Stem Cells: Perspectives for Therapeutic Applications - M. Ferrari; A. Corradi; M. Lazzaretti; M. De’Cillà; C. G. Losi; R. Villa; A. Lanfranchi (Veterinary Research Communications, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Fruit and vegetable consumption and lymphoma risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Sabine Rohrmann; Nikolaus Becker; Jakob Linseisen; Alexandra Nieters; Thomas Rüdiger; Ole Raaschou-Nielsen; Anne Tjønneland; Hans E. Johnsen; Kim Overvad; Rudolf Kaaks; Manuela M. Bergmann; Heiner Boeing; et al. (Cancer Causes & Control, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Imported malaria at Italy’s National Institute for Infectious Diseases Lazzaro Spallanzani, 1984–2003 - F. Spinazzola; E. Nicastri; C. Vlassi; P. Ghirga; M. Marco; S. Pittalis; M. G. Paglia; C. Ferrari; P. Narciso (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

An Immunoenzyme Linked Assay (ELISA) for the Detection of Antibodies to Truncated Glycoprotein D (tgD) of Bovine Herpesvirus-1 - S. Petrini; M. Ferrari; S. Vincenzetti; A. Vita; A. Amici; G. Ramadori (Veterinary Research Communications, 2006)

Bone Mineral Density in Two Boxer Dogs Affected by Moderate to End-stage Chronic Renal Failure - A. Zotti; M. Caldin; E. Vettorato; V. Ferrari; L. Cavicchioli; D. Bernardini (Veterinary Research Communications, 2006)

The Effective Dispersion of Nanovectors Within the Tumor Microvasculature - P. Decuzzi; F. Causa; M. Ferrari; P. A. Netti (Annals of Biomedical Engineering, 2006)

Blood Compatibility of Cetyl Alcohol/Polysorbate-Based Nanoparticles - J. M. Koziara; J. J. Oh; W. S. Akers; S. P. Ferraris; R. J. Mumper (Pharmaceutical Research, 2005)

Study on the Virulence, Cell-mediated Immune Response and Histolesivity of Three Field PRRSV Strains with an ORF 5 Genetic Variation - A. Corradi; M. Ferrari; A. M. Cantoni; C. Robotti; L. Alborali; R. Di Lecce; P. Candotti; G. P. Sandri; P. Borghetti (Veterinary Research Communications, 2005)

Vaccination Trials Against Bovine Herpesvirus-1 - G. Castrucci; M. Ferrari; D. Salvatori; S. Sardonini; F. Frigeri; S. Petrini; M. Lo Dico; C. Marchini; A. Rotola; A. Amici; M. Provinciali; A. Tosini; et al. (Veterinary Research Communications, 2005)

X-linked heterochromatin distribution in the holocentric chromosomes of the green apple aphid Aphis pomi - A. Criniti; G. Simonazzi; S. Cassanelli; M. Ferrari; D. Bizzaro; G. C. Manicardi (Genetica, 2005)

A Theoretical Model for the Margination of Particles within Blood Vessels - P. Decuzzi; S. Lee; B. Bhushan; M. Ferrari (Annals of Biomedical Engineering, 2005)

Loading of nutrient from a land-based fish farm(Orbetello, Italy) at different times - S. Porrello; M. Lenzi; G. Ferrari; E. Persia; F. Savelli; P Tomassetti (Aquaculture International, 2005)

Evaluation of Endogenous Pig Retrovirus Expression and of Tumorigenicity in Nude Mice - M. Ferrari; A. Corradi; P.G. Petronini; A. Tosini; A. Toniolo; C. Robotti; R. Moratti (Veterinary Research Communications, 2004)

Segmentation of the fibro-glandular disc in mammogrms using Gaussian mixture modelling - R. J. Ferrari; R. M. Rangayyan; R. A. Borges; A. F. Frère (Medical & Biological Engineering & Computing, 2004)

Characterization and metal affinity of Tirofiban, a pharmaceutical compound used in acute coronary syndromes - E. Ferrari; L. Menabue; M. Saladini (BioMetals, 2004)

Identification of the breast boundary in mammograms using active contour models - R. J. Ferrari; A. F. Frère; R. M. Rangayyan; J. E. L. Desautels; R. A. Borges (Medical & Biological Engineering & Computing, 2004)

The role of host sex in parasite dynamics: field experiments on the yellow‐necked mouse Apodemus flavicollis - Nicola Ferrari; Isabella M. Cattadori; Javier Nespereira; Annapaola Rizzoli; Peter J. Hudson (Ecology Letters, 2004)
We investigated the role of host sex in parasite transmission and questioned: ‘Is host sex important in influencing the dynamics of infection in free living animal populations?’ We experimentally reduced the helminth community of either males or females in a yellow‐necked mice ( Apodemus flavicollis ) population using an anthelmintic, in replicated trapping areas, and subsequently monitored the prevalence and intensity of macroparasites in the untreated sex. We focussed on the dominant parasite Heligmosomoides polygyrus and found that reducing parasites in males caused a consistent reduction of parasitic intensity in females, estimated through faecal egg counts, but the removal of parasites in females had no significant influence on the parasites in males. This finding suggests that males are responsible for driving the parasite infection in the host population and females may play a relatively trivial role. The possible mechanisms promoting such patterns are discussed.

Sigmoidal exsolution by internal shear stress in pyroxenes from chondritic meteorites - C. Ferraris; L. Folco; M. Mellini (Physics and Chemistry of Minerals, 2003)

Dietary P regulates phosphate transporter expression, phosphatase activity, and effluent P partitioning in trout culture - R. M. Coloso; K. King; J. W. Fletcher; P. Weis; A. Werner; R. P. Ferraris (Journal of Comparative Physiology B, 2003)

Molecular detection of cell line cross-contaminations using amplified fragment length polymorphism DNA fingerprinting technology - E. Milanesi; P. Ajmone-Marsan; E. Bignotti; M. N. Losio; J. Bernardi; F. Chegdani; M. Soncini; M. Ferrari (In Vitro Cellular & Developmental Biology - Animal, 2003)

Chemical Attractants in Horseshoe Crab, Limulus polyphemus, Eggs: The Potential for an Artificial Bait - Kirstin M. Ferrari; Nancy M. Targett (Journal of Chemical Ecology, 2003)

Characterization of Endogenous Retroviruses in Pig Cell Cultures - M. Ferrari; M.N. Losio; A. Corradi; S. Vittori; A. Tosini (Veterinary Research Communications, 2003)

MOLECULAR DETECTION OF CELL LINE CROSS-CONTAMINATIONS USING AMPLIFIED FRAGMENT LENGTH POLYMORPHISM DNA FINGERPRINTING TECHNOLOGY - E. MILANESI; P. AJMONE-MARSAN; E. BIGNOTTI; M. N. LOSIO; J. BERNARDI; F. CHEGDANI; M. SONCINI; M. FERRARI (In Vitro Cellular & Developmental Biology - Animal, 2003)

Calf and shin muscle oxygenation patterns and femoral artery blood flow during dynamic plantar flexion exercise in humans - S. Shimizu; F. Chiarotti; M. Ferrari; A. Kagaya; V. Quaresima; S. Homma; K. Azuma (European Journal of Applied Physiology, 2001)

Tadpoles Assay: Its Application to a Water Toxicity Assessment of a Polluted Urban River - S. O. Demichelis; F. R. de la Torre; L. Ferrari; M. E. García; A. Salibián (Environmental Monitoring and Assessment, 2001)

Effects of Human Colonization on the Abundance and Diversity of Mammals in Eastern Brazilian Amazonia - M. Aparecida Lopes; Stephen F. Ferrari (Conservation Biology, 2000)

Effects of Human Colonization on the Abundance and Diversity of Mammals in Eastern Brazilian Amazonia - M. Aparecida Lopes; Stephen F. Ferrari (Conservation Biology, 2000)
With its long history of colonization, eastern Amazonia has the highest population density in Brazilian Amazonia and represents the typical pattern of recent human occupation. Between 1991 and 1995, we surveyed the mammalian fauna at five sites, representing different degrees of human disturbance. We used line transects (1511 km surveyed) to describe differences in diversity and abundance at each site and to evaluate the effects of environmental factors. Twenty‐two of the expected 44 species were recorded during surveys, but no more than 18 were recorded at any one site, and only 3 species were observed at all five sites. Despite a minimum transect length of 202 km, most species were recorded relatively infrequently at all sites, although overall sighting rates at different sites varied by more than 100%. Between‐site differences were even more pronounced when we compared specific groups (e.g., arboreal, terrestrial, game, nongame), reflecting the differential effects of factors such as hunting, logging, and forest clearing. In general terms, species diversity, abundance, total biomass, and mean biomass all tended to decrease with increasing human disturbance. Two more specific patterns were also distinguished: decreasing abundance and biomass of game species with increasing hunting pressure and increasing abundance of nongame species with increasing forest disturbance. Intense hunting pressure alone may have deleterious short‐term effects on abundance, but not necessarily on diversity, whereas prolonged hunting pressure, combined with forest clearing, results in marked distortions in the mammalian community. Overall, the study emphasizes the relative paucity of the mammalian fauna of eastern Amazonia, in terms of both species diversity and abundance, and its vulnerability to the ongoing process of human colonization in the region.

Is a Kit for Identification of Clinical Yeasts Correctly Evaluated When Released onto the Market? - A. M. Tortorano; F. Barchiesi; E. Manso; M. T. Montagna; C. Farina; L. Ferrari; A. Raballo; A. Grancini; G. Lombardi (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Relationship between sediment distribution and Posidonia oceanica seagrass - G. De Falco; S. Ferrari; G. Cancemi; M. Baroli (Geo-Marine Letters, 2000)

Dietary phosphorus regulates intestinal transport and plasma concentrations of phosphate in rainbow trout - E. M. Avila; H. Tu; S. Basantes; R. P. Ferraris (Journal of Comparative Physiology B, 2000)

An artificial grasping evaluation system for the paralysed hand - M. C. Ferrari de Castro; A. Cliquet (Medical & Biological Engineering & Computing, 2000)

Titi monkeys (Callicebus spp., Atelidae: Platyrrhini) in the Brazilian state of Rondônia - Stephen F. Ferrari; Simone Iwanaga; Mariluce R. Messias; Eleildon M. Ramos; Paulo C. S. Ramos; Ernesto H. da Cruz Neto; Paulo E. G. Coutinho (Primates, 2000)

Tissue inhibitors of metalloproteases: Regulation and biological activities - Gianfranco Fassina; Nicoletta Ferrari; Claudio Brigati; Roberto Benelli; Leonardo Santi; Douglas M. Noonan; Adriana Albini (Clinical & Experimental Metastasis, 2000)

Zoogeography of Chiropotes albinasus (Platyrrhini, Atelidae) in Southwestern Amazonia - Stephen F. Ferrari; Simone Iwanaga; Paulo E. G. Coutinho; Mariluce R. Messias; Ernesto H. Cruz Neto; Eleildon M. Ramos; Paulo C. S. Ramos (International Journal of Primatology, 1999)

Synchrotron powder diffraction study of phengite 3T from the Dora-Maira massif: P - V - T equation of state and petrological consequences - A. Pavese; G. Ferraris; V. Pischedda; M. Mezouar (Physics and Chemistry of Minerals, 1999)

Effects of a short-term strength training programme on lymphocyte subsets at rest in elderly humans - S. Bermon; P. Philip; P. Ferrari; M. Candito; C. Dolisi (European Journal of Applied Physiology, 1999)

Catechol(amine)s as probes of lactoperoxidase catalytic site structure: spectroscopic and modeling studies - R. P. Ferrari; Silvio Traversa; Luca De Gioia; Piercarlo Fantucci; Gianpaolo Suriano; Elena M. Ghibaudi (JBIC Journal of Biological Inorganic Chemistry, 1999)

Acetylcholinesterase assay may predict cognitive response of Alzheimer patients to eptastigmine treatment - B. P. Imbimbo; M. Nicoli; C. Martini; G. P. Tomelleri; P. Martelli; G. P. Ferrari; G. Gambina (European Journal of Clinical Pharmacology, 1998)

MALE HUMPBACK WHALE DIES IN COMPETITIVE GROUP - Adam A. Pack; Dan R. Salden; Mark J. Ferrari; Debbie A. Glockner‐Ferrari; Louis M. Herman; Harrison A. Stubbs; Janice M. Straley (Marine Mammal Science, 1998)

Electrophoretic Polymorphisms and Their Taxonomic Implications in Callitrichini (Primates, Platyrrhini) - C. M. Meireles; J. Czelusniak; I. Sampaio; H. Schneider; S. F. Ferrari; A. F. Coimbra-Filho; A. Pissinatti; J. A. P. C. Muniz; H. S. Ferreira; M. P. C. Schneider (Biochemical Genetics, 1998)

Multiple testing in fetal gender determination from maternal blood by polymerase chain reaction - Fiorenza Lagona; M. Smid; Nadia Papasergio; Augusto Ferrari; Maurizio Ferrari; Laura Cremonesi (Human Genetics, 1998)

Changing Concentrations of Cu, Zn, Cd and Pb in a High Altitude Peat Bog from Bolivia during the Past Three Centuries - E. Espi; C.F. Boutron; S. Hong; M. Pourchet; C. Ferrari; W. Shotyk; L. Charlet (Water, Air, & Soil Pollution, 1997)

P-V equation of state of portlandite, Ca(OH) 2 , from powder neutron diffraction data - A. Pavese; M. Catti; G. Ferraris; S. Hull (Physics and Chemistry of Minerals, 1997)

Polyclonal origin of medullary carcinoma of the thyroid in multiple endocrine neoplasia type 2 - A. M. Ferraris; Rosa Mangerini; Gian Franco Gaetani; Cristina Romei; Aldo Pinchera; Furio Pacini (Human Genetics, 1997)

Cytogenetic biomonitoring of styrene-exposed plastic boat builders - M. Artuso; G. Angotzi; S. Bonassi; S. Bonatti; M. De Ferrari; D. Gargano; L. Lastrucci; L. Miligi; C. Sbrana; A. Abbondandolo (Archives of Environmental Contamination and Toxicology, 1995)

Isolation and characterization of cytopathic strains of rotavirus from rabbits - G. Castrucci; M. Ferrari; F. Frigeri; V. Cilli; L. Perucca; G. Donelli (Archives of Virology, 1985)

Reactivation in calves ofBovid herpesvirus 2 latent infection - G. Castrucci; M. Ferrari; F. Frigeri; S. Ranucci; V. Cilli; B. Tesei; L. Rampichini (Archives of Virology, 1982)